Examining the impact of early longitudinal patient exposure on medical students’ career choices - Kwok, Jason; Wu, Vincent; Sanfilippo, Anthony; Bowes, Kathryn; Pinchin, Sheila (Canadian Medical Education Journal, 2017)
Background: Medical schools include career direction experiences to help students make informed career decisions. Most experiences are short, precluding students from attaining adequate exposure to long-term encounters within medicine. We investigated the impact of the First Patient Program (FPP), which fosters longitudinal patient exposure by pairing junior medical students with chronically ill patients through their healthcare journey, in instilling career direction. Methods: Medical students who completed at least 6-months in the FPP participated in a cross-sectional survey. Students’ answers were analyzed with respect to the number of FPP appointments attended. Thematic analysis was conducted to explore qualitative responses. Results: One hundred and forty-eight students participated in the survey. Only 28 (19%) students stated that the FPP informed their career decisions. Thirty-nine percent of students who attended four or more appointments indicated that the FPP informed their career decisions, compared to 16% of students who attended less (p=0.021). Thematic analysis revealed two themes: 1) Students focused mainly on patient encounters within FPP; and 2) Students sought career directions from other experiences. Conclusion: The majority of students did not attain career guidance from the FPP, but rather used the program to understand the impact of chronic illness from the patient’s perspective.